Effects of Matrix Metalloproteinases on the Performance of Platelet Fibrin Gel Spiked With Cardiac Stem Cells in Heart Repair - Shen, Deliang (Stem Cells Transl Med, 2016)
Stem cells and biomaterials have been studied for therapeutic cardiac repair. Previous studies have shown the beneficial effects of platelet fibrin gel and cardiac stem cells when cotransplanted into rodent hearts with myocardial infarction (MI). We hypothesized that matrix metalloproteinases (MMPs) play an important role in such protection. Thus, the present study is designed to elucidate the effects of MMP inhibition on the therapeutic benefits of intramyocardial injection of platelet fibrin gel spiked with cardiac stem cells (cell-gel) in a rat model of acute MI. In vitro, broad-spectrum MMP inhibitor GM6001 undermines cell spreading and cardiomyocyte contraction. In a syngeneic rat model of myocardial infarction, MMP inhibition blunted the recruitment of endogenous cardiovascular cells into the injected biomaterials, therefore hindering de novo angiogenesis and cardiomyogenesis. Echocardiography and histology 3 weeks after treatment revealed that metalloproteinase inhibition diminished the functional and structural benefits of cell-gel in treating MI. Reduction of host angiogenesis, cardiomyocyte cycling, and MMP-2 activities was evident in animals treated with GM6001. Our findings suggest that MMPs play a critical role in the therapeutic benefits of platelet fibrin gel spiked with cardiac stem cells for treating MI. SIGNIFICANCE: In this study, the effects of matrix metalloproteinase inhibition on the performance of platelet gel spiked with cardiac stem cells (cell-gel) for heart regeneration are explored. The results demonstrate that matrix metalloproteinases are required for cell-gel to exert its benefits in cardiac repair. Inhibition of matrix metalloproteinases reduces cell engraftment, host angiogenesis, and recruitment of endogenous cardiovascular cells in rats with heart attack.